2020
DOI: 10.3389/fonc.2020.584022
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment Serum HE4 Level as a Novel Independent Prognostic Biomarker for Uterine Cervical Carcinoma Patients

Abstract: In spite of the effective implementation of screening programs, uterine cervical carcinoma (UCC) remains one of the major causes of cancer death among women around the world. The aim of this study was to investigate the prognostic value of serum human epididymis protein 4 (HE4) in UCC. Pre-treatment serum samples from 109 UCC patients and 99 healthy women were analyzed for HE4 levels by a quantitative chemiluminescent microparticle immunoassay on the automated ARCHITECT instrument. HE4 serum (sHE4) levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…The results demonstrated that GTSF1L and GNG8 exhibited a gradually decreasing tendency along with the disease progression, and GTSF1L showed greater expression disparity (Figure 9A). CA125 (MUC16), CEA (CEACAM5), and HE4 (WFDC2) are clinically established diagnostic and prognostic markers of CESC; high levels of these biomarkers suggest cancer progression and poor prognosis (18,19). Here, we found that the expression level of GTSF1L in CESC displayed a significantly negative relationship with these biomarkers (Figures 9B and S12A), which was relatively consistent with the better prognosis observed in the GTSF1L-high patient group.…”
Section: The Role Of Gtsf1l In Immune Contexture and Clinical Practicesupporting
confidence: 81%
“…The results demonstrated that GTSF1L and GNG8 exhibited a gradually decreasing tendency along with the disease progression, and GTSF1L showed greater expression disparity (Figure 9A). CA125 (MUC16), CEA (CEACAM5), and HE4 (WFDC2) are clinically established diagnostic and prognostic markers of CESC; high levels of these biomarkers suggest cancer progression and poor prognosis (18,19). Here, we found that the expression level of GTSF1L in CESC displayed a significantly negative relationship with these biomarkers (Figures 9B and S12A), which was relatively consistent with the better prognosis observed in the GTSF1L-high patient group.…”
Section: The Role Of Gtsf1l In Immune Contexture and Clinical Practicesupporting
confidence: 81%
“…A more recent study evaluating the role of pre-treatment serum HE4 levels in cervical cancer reported that serum HE4 could be a preoperative tumor biomarker of poor prognosis in cervical cancer. 29 Consistent with our own results, this study also demonstrated that higher levels of serum HE4 correlate with advanced stage, larger tumor size, and high tumor grade, while no significant association was found with LVSI, PM involvement, and LN involvement, which is not consistent with our study.…”
Section: Discussionsupporting
confidence: 79%
“…28,35 In other previous studies, serum HE4 levels were higher in cervical cancer patients compared to healthy controls, but lower than ovarian cancer patients, showing similar results to our study. 28,29 This study has several limitations. First, the existence of underlying selection bias is possible due to the retrospective design.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Currently, alterations in CA125 and SCC antigen levels are more likely to predict CC outcomes [15,16]. Moreover, HE4 is a prognostic marker for survival in individuals who have high risk of CC [17]. Recent studies have shown that serum SCC is a better biomarker, with a sensitivity of 80% in patients with CC [18,19].…”
Section: Discussionmentioning
confidence: 99%